Fictional and Historical Worlds - Hart, J. author. aut Link
XIII, 264 p.
Keywords: Examines possible and fictional worlds, author and authority, otherness and recognition, translation, alternative critique, empire, education, imagination, comedy, history, poetry, and culture. The analyzed works include classical and modern texts and theorists of the past sixty years ranging from Jerome Bruner to Stephen Greenblatt.